Glycoproteomics: Past, present and future - Tissot, Bérangère; North, Simon J.; Ceroni, Alessio; Pang, Poh-Choo; Panico, Maria; Rosati, Floriana; Capone, Antonietta; Haslam, Stuart M.; Dell, Anne; Morris, Howard R. (FEBS letters, 2009)
This invited paper reviews the study of protein glycosylation, commonly known as glycoproteomics, beginning with the origins of the subject area in the early 1970s shortly after mass spectrometry was first applied to protein sequencing. We go on to describe current analytical approaches to glycoproteomic analyses, with exemplar projects presented in the form of the complex story of human glycodelin and the characterisation of blood group H eptitopes on the O-glycans of gp273 from Unio elongatulus. Finally, we present an update on the latest progress in the field of automated and semi-automated interpretation and annotation of these data in the form of GlycoWorkBench, a powerful informatics tool that provides valuable assistance in unravelling the complexities of glycoproteomic studies.